A Modifying the Instrument of Self-Regulation in Early Childhood Assessment - Pangestuti, Retno; Kadiyono, Anissa Lestari; Cahyadi, Surya; Agustiani, Hendriati (Jurnal Pendidikan Usia Dini, 2019)
Self-regulation for preschool children is very important to support children’s adjustments in all situations and conditions. The current problem is the instrument of self-regulation is more focused on regulation in learning which is not suitable for young children. This study aims to examine the validity and reliability of Preschool Self-Regulation Assessment (PSRA) in Indonesia by modifying several children self-regulation theories. The instrument was translated from English into Indonesian and it retranslated into the native language by linguists. The questions, then, were validated through a process of professional judgment and cognitive de-briefing. The study was carried out to 179 children aged 6 to 7 years old. Data were analyzed by using confirmatory factor analysis (CFA). It showed that there are 5 dimensions of children's self-regulation, namely: attentional focus, behavioral control, self-motivated, self-autonomy and emotional control. The result showed that the five-dimensional model is agreed with the data and prove to measure children’s self-regulation. Cronbach’s alpha coefficient value was 0.899, indicating high scale reliability. Thus, the preschool children’s self-regulation assessment has well psychometric for further use. Keywords: Children’s self-regulation, Confirmatory Factor Analysis, Construct validation, Pre-school self-regulation assessment, Reliability References Amanda, N. ., Antara, P. ., & Magta, M. (2016). Hubungan Pola Asuh Orangtua dengan Regulasi Diri Anak Usia 5-6 Tahun. Journal Pendidikan Anak Usia Dini Universitas Pendidikan Ganesha, 4(2), 1–11. Bentley, J. J. (2013). Parental Involvement, Parent-Child Warmth and School Engagement as Mediated by Self-Regulation. Brigham Young University. Bierman, K. L., Domitrovich, C. E., Nix, R. L., Welsh, J. A., Greenberg, M. T., Blair, C., … Gill, S. (2008). Promoting academic and social-emotional school readiness: The Head Start REDI program. Child Development, 79(6). Blair, C., & Diamond. (2008). Developing your Children Self-Regulation through Everyday Experiences. Blair, C., & Raver, C. C. (2015). School readiness and self-regulation: A developmental psychobiological approach. Annual Review of Psychology, 66, 711–731. Eisenberg, N., Hofer, C., & Vaughan, J. (2007). Effortful Control and Its Socioemotional Consequences. In J. J. Gross (Ed.), Handbook of emotion regulation (hal. 287–306). New York: Guilford Press. Eisenberg, N., Spinrad, T. L., & Eggum, N. D. (2010). Emotion-Related Self-Regulation and Its Relation to Children’s Maladjustment. Annual Reviews Clinical Psychology, 27(6), 495–525. Eisenberg, N., Valiente, C., & D.Eggum, N. (2010). Self-Regulation and School Readiness. Early Education Development., 21(5), 681–698. Goyette, P., Carrol, K., Smith-Donald, R., Metzger, M., Young, T., & Raver, C. C. (2006). Field Administration of an Emotional and Behavioral Assessment of Head Start Children:Preliminary Findings from the Preschool Self-Regulation Assessment. Grolnick, W. S., & Farkas, M. (2002). Parenting and the development of children’s self-regulation. In M. H. Bornstein (Ed.), Handbook of parenting (Vol. 5, hal. 89–110). Practical issues in parenting. Pino, D., & Whitebread, D. (2010). The Role of Parenting in Children’s Self-Regulated Learning. Educational Research Review, 5(3), 220–242. Raver, C. C., Jones, S. M., Li-Grining, C., Zhai, F., Bub, K., & Pressler, E. (2011). CSRP’s impact on low-income preschoolers’ pre-academic skills: Self-regulation and teacher-student relationships as two mediating mechanisms. Child Development, 82(1), 362–378. Rimm-Kaufman, S. E., Curby, T. W., Grimm, K. J., Nathanson, L., & Brock, L. L. (2009). The contribution of children’s self-regulation and classroom quality to children’s adaptive behaviors in the kindergarten classroom. Developmental Psychology, 45(4). Rochmah, S. N. (2017). Hubungan Konsep Diri Guru Terhadap Regulasi Diri Anak Usia Dini. Jurnal Tunas Siliwangi SPS UPI, 3(2), 160–174. Smith-Donald, R., Carroll, K., Goyette, P., Metzger, M., Young, T., & Raver, C. C. (2006). Preliminary Validity of the Preschool Self-Regulation Assessment (PSRA). Smith-Donald, R., Raver, C. C., Hayes, T., & Richardson, B. (2007). Preliminary construct and concurrent validity of the Preschool Self-regulation Assessment (PSRA) for field-based research. Early Childhood Research Quarterly, 22(2), 173–187. Tanribuyurdu, Findik, E., Yildiz, & Guler, T. (2014). Preschool Self-Regulation Assessment (PSRA): Adaptation Study for Turkey. Education and Science, 39(176), 317–328. Wang, L., Hamaker, E., & Bergeman, C. (2014). Investigating inter-individual differences in short-term intra-individual variability. Psychological Methods, 17(4), 2012. Zimmerman, B. (2002). Becoming a Self-Regulated Learner: An Overview. Theory Into Practice, 41(2), 64–70.